How social interactions can affect Modern Code Review - Ciancarini, Paolo; Kruglov, Artem; Malikova, Aygul; Pedrycz, Witold; Succi, Giancarlo (Frontiers in Computer Science, 2023)
This paper presents a study on the non-technical issues in the Modern Code Review (MCR) process. MCR is a multistage process where developers evaluate source code written by others to enhance the software quality. The effects of MCR have been studied in many researches, with experiments conducted at large software companies and in open-source projects. However, the possible solutions to non-technical issues in the MCR process are not well-studied. This study aims not only at investigating social problems described above but also at finding possible ways to prevent them and improve the overall quality of the MCR process. Specifically, we applied the grounded theory research shaped by GQM approach to collect data on the attitudes of developers from different teams towards MCR. We conducted interviews with 25 software developers from 13 companies to obtain the information necessary to investigate how social interactions affect the code reviewing process. We found out the consequences of interpersonal relationships within the team and received a list of possible strategies to overcome these problems.